PHARMACOGNOSTICAL AND PHYTO-CHEMICAL EVALUATION OF PIPPALYADI YOGA: A POLYHERBAL FORMULATION - Shachi Hemantkumar, Pandya; Dhiman, Kamini; Dei, L. P.; Thakar, A. B.; Harisha, C R (International Journal of Ayurveda and Pharma Research, 2015)
Pippalyadi Yoga is Churna Kalpana described by Acharya Chakrapani in Vandhyatva (infertility). Ovulatory dysfunction is the prime cause of Infertility among the world, Pippalyadi Yoga is useful in patients especially having Anovulation which is known as Abeejatva in Ayurveda. So a new pharmaceutical preparation Pippalyadi Yoga in the form of Churna (powder) was tried to standardize which is economical in terms of time and machinery usage. Pharmacognostical and phyto-chemical observations revealed the specific characters of all active constituents used in the preparation. The present work was carried out to standardize the finished product of Pippalyadi Yoga to confirm its identity, quality and purity. The presence of stone cells, oil globules, olio resin cells, parenchymatous cells, oval & beaker shaped starch grains, pollen grains were the characteristic features observed in the microscopy of the prepared drug. Phyto-chemical analysis showed Loss on drying 10.07 % w/w, ash value 6.55 %w/w, water soluble extract 14 % w/w, methanol soluble 13.40 % w/w, particle consistency above 60 mesh 4.10 % w/w, between 60-85 mesh 9.20 % w/w, between 85-120 mesh 13.30 % w/w & below 120 mesh 73.37 % w/w & pH 5.0. HPTLC of Pippalyadi Yoga is the preliminary quantitative analysis which shows 8 prominent spots at Rf. 0.09, 0.61, 0.67, 0.74, 0.80, 0.86, 0.91, 1.00 in UV 254 nm and 7 prominent spots at Rf. 0.06, 0.17, 0.63, 0.67, 0.75, 0.82, 0.88 in UV 366 nm. Pippalyadi Yoga, a polyherbal formulation of 4 ingredients was prepared and HPTLC finger print profile was developed and it can be considered pharmacopial standard of Pippalyadi Yoga.